Building Brand Image through Innovative Principal Leadership: A Case Study of State Junior High School 35, Tebo, Indonesia - Rizky Amelia Hasibuan; Boby Yasman Purnama (Tuah Foundation, 2025)
Increasing competition among junior high schools necessitates that principals employ innovative strategies to establish a positive brand image State Junior High School 35 in Tebo Regency faces persistent challenges, including declining new student enrollment over the past three years, limited facilities and infrastructure, and a less strategic location. This study analyzes the principal’s innovative leadership in enhancing brand image, examines supporting and inhibiting factors, and evaluates innovation effectiveness. Using a qualitative descriptive method, data were gathered through observation, interviews with the principal, vice principals, and teachers, and document analysis, followed by thematic analysis to identify innovation patterns and influencing factors. Findings indicate that innovations include improving academic and non-academic achievements, upgrading facilities and infrastructure, implementing a Green School program, promoting active–creative–enjoyable learning, integrating educational technology, digitalizing school promotion, and fostering alumni development to secure admission to prestigious higher-level schools. These initiatives have positively influenced the school’s image but remain constrained by budget limitations, inadequate internet connectivity, and modest student numbers. Supporting factors comprise the principal’s commitment and active participation from the school community, while obstacles involve limited resources, suboptimal facilities, and location disadvantages. Overall, innovative leadership strengthens brand image but has not fully reversed declining enrollment. The study recommends enhanced local government support through improved infrastructure, expanded digital promotion, and leadership innovation training for schools in rural or remote areas. This innovation model offers a practical framework for other schools confronting similar contextual constraints in building a competitive brand image.